Factors Predicting Hypothyroidism in Long-Term Follow-Up after131I Therapy - Gimlette, T. M. D.; Critchley, M.; Squire, C. R. (Nuklearmedizin - NuclearMedicine, 1988)
187 patients, euthyroid for more than a year after radioiodine treatment for hyperthyroidism, were studied for 10 years; 81 (43%) became hypothyroid. The incidence of hypothyroidism was lower in patients initially presenting with large thyroids (28%) or with nodular thyroids (22%) and in those without thyroid autoantibodies (31 %). During follow-up, an elevated serum TSH was present in all 81 patients when they became hypothyroid (sensitivity and negative predictive value 100%), and was present for at least a year in 98% of these. However, an elevated serum TSH was also present in 48% of 106 patients remaining euthyroid (positive predictive value 61 %). FT4I was low in 94% of patients who became hypothyroid and normal in 80% of patients who remained euthyroid (positive predictive value 78%, negative predictive value 93%). Serum TSH and FT4I were the best biochemical predictors. FT3I and serum cholesterol were less satisfactory. A palpable thyroid becoming impalpable, though readily assessed, was limited in usefulness. Clinical appraisal remains important and a progressive, though perhaps less rapid, later increase in the incidence of hypothyroidism appears likely.